Money market funds in Europe and financial stability - Julie Ansidei; Elias Bengtsson; Daniele Frison; Giles Ward (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2012)
Money market funds (MMFs) are investment funds whose primary objectives are to maintain the principal value of the funds and offer a return in line with money market rates, while providing daily liquidity to their investors. In Europe, MMFs manage approximately EUR 1 trillion in assets, with three countries (France, Ireland and Luxembourg) representing an aggregate market share of over 90%. MMFs were at the heart of dramatic episodes of the financial crisis of 2007-08, prompting regulators on both sides of the Atlantic to extensively review the regulatory framework applicable to them. In Europe, new guidelines were adopted in 2010, imposing strict standards in terms of the credit quality and maturity of underlying securities and better disclosure to investors. Although these initiatives are considered to have considerably improved MMF regulation, discussions are still ongoing, both in the United States (US) and at the international level, as to how to reduce the systemic risks associated with MMFs and, in particular, their vulnerability to runs. The Financial Stability Board (FSB) has identified MMFs as a key component of the shadow banking system and has asked the International Organization of Securities Commissions (IOSCO) to submit policy recommendations by July 2012 for further regulatory reform of such funds. The purpose of this occasional paper is to provide a first assessment of the systemic importance of MMFs within the European context, as well as of the main areas of risk, policy implications and the possible role for the European Systemic Risk Board (ESRB).
Keywords: G15; G18; 330; ESRB; financial stability; money market funds; shadow banking